A Rare Case of Auricular Angiolymphoid Hyperplasia With Eosinophilia Associated With Chronic Hearing Aid Use - Ayat Shawish; Maher Raslan; Reem Khabbaza; Mohammad Adib Houreih; Moatasem Hussein Al‐Janabi; Fouz Hassan (Clinical Case Reports, 2026)
ABSTRACT Evaluating external device‐related friction is essential when managing localized auricular vascular lesions. Clinicians should recognize that angiolymphoid hyperplasia with eosinophilia (ALHE) can arise secondary to chronic mechanical irritation and may present with minimal tissue eosinophilia.